NON-MARINE PERMIAN BIOSTRATIGRAPHY AND BIOCHRONOLOGY: AN INTRODUCTION - Lucas S.G.; Schneider J.W.; Cassinis G. (My University, 2006)
The Permian time scale based on marine rocks and fossils is well defined and of global utility, but non-marine Permian biostratigraphy and chronology is in an early phase of development. Non-marine Permian strata are best known from western Europe and the western United States, but significant records are also known from Russia, South Africa, China and Brazil. Global time terms based on non-marine Permian strata, such as Rotliegend, Zechstein, Autunian, Saxonian and Thuringian, are either inadequately defined or poorly characterized and should only be used as lithostratigraphic terms. Macro- and microfloras have long been important in non-marine Permian correlations, but are subject to limitations based on palaeoprovinciality and facies/climatic controls. Charophytes, conchostracaus, ostracodes and freshwater bivalves have a potential use in non-marine Permian biostratigraphy but are limited by their over-split taxonomy and lack of well-established stratigraphic distributions of low-level taxa. Tetrapod footprints provide poor biostratigraphic resolution during the Permian, but tetrapod body fossils and insects provide more detailed biostratigraphic zonations, especially in the Lower Permian. Numerous radioisotopic ages are available from non-marine Permian sections and need to be more precisely correlated to the global time scale. The Middle Permian Illawarra reversal and subsequent magnetic polarity shifts are also of value to correlation. There needs to be a concerted effort to develop non-marine Permian biostratigraphy, to correlate it to radio-isotopic and magnetostratigraphic data, and to cross-correlate it to the marine time scale. © The Geological Society of London.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская